Macrophomina phaseolina associated with grapevine decline in Iran - ABED-ASHTIANI, Farnaz; NARMANI, Abolfazl; ARZANLOU, Mahdi (Phytopathologia Mediterranea, 2018)
Grapevines exhibiting general decline symptoms were observed in July 2012 in Arbatan, a region in Marand county, north-western Iran. Leaf necrosis symptoms were also observed in affected grapevines. Dark brown necrotic lesions and wood discoloration were observed in the vascular tissues of affected cordons. Fungal isolates, all with similar cultural and morphological features, were obtained from symptomatic tissues. Morphological characteristics indicated that the isolates were Macrophomina phaseolina. Sequence analysis of the elongation factor (EF-1α) gene from isolates confirmed this identification, with 100% similarity to the reference M. phaseolina sequences obtained from GenBank. Pathogenicity assays of two M. phaseolina isolates on 2-year-old potted vines (cv. ‘Keshmeshi’) demonstrated that M. phaseolina was pathogenic on grapevine. This study confirmed the association of M. phaseolina with grapevine decline symptoms, and represents the first report of this fungus associated with grapevine trunk diseases in Iran.